2020
DOI: 10.3390/su12155969
|View full text |Cite
|
Sign up to set email alerts
|

Relaxing Effect Induced by Forest Sound in Patients with Gambling Disorder

Abstract: The number of people addicted to gambling has increased worldwide. They often suffer from debilitating medical conditions associated with stress or depression. This study examined the physiological and psychological reactions of gambling disorder (GD) patients while listening to high-definition forest or city sounds using headphones. In total, 12 Japanese male GD patients were exposed to high-definition forest or city sound waves for 1 min via headphones. Near-infrared spectroscopy of the prefrontal cortex was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
2
12
0
1
Order By: Relevance
“…In this regard, previous studies analyzing the correlation between the PFC and the natural envi-ronment secured evidence that blood flow in the FL area decreased after exposure to natural environments such as forests or gardens. These findings have thus demonstrated that the natural environment helps to reduce blood flow in the FL, thereby reducing mental stress (Lee et al, 2015;Song et al, 2018;Song et al, 2020;Ochiai et al, 2020).…”
Section: Introductionmentioning
confidence: 75%
“…In this regard, previous studies analyzing the correlation between the PFC and the natural envi-ronment secured evidence that blood flow in the FL area decreased after exposure to natural environments such as forests or gardens. These findings have thus demonstrated that the natural environment helps to reduce blood flow in the FL, thereby reducing mental stress (Lee et al, 2015;Song et al, 2018;Song et al, 2020;Ochiai et al, 2020).…”
Section: Introductionmentioning
confidence: 75%
“…Auditory stimulation by the forest, such as the sound of leaves shaking in the wind, singing birds, and the sound of flowing streams, can contribute to psychophysical relaxation and stress recovery [ 102 , 103 , 104 ]. For example, Zhang et al [ 103 ] reported that the acoustic and visual comfort given in the green environment had a strong positive correlation with low depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, acoustic comfort showed a more significant influence than visual comfort. In addition, Ochiai et al [ 104 ] reported that as a result of a survey of the effects of forest sound on gambling addicts, forest sound significantly reduced depression and tension-anxiety rather than urban sound. Thus, it has been proven that visual and auditory stimuli in the forest can significantly improve emotional depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the major data sources of the two kinds of evaluation in China is the primary data on the participants, while the data source in other countries are relatively diverse, such as use of smartphones [105], data from centers for disease control or similar departments [97] and national projects [106]. Furthermore, Chinese researchers mainly use either subjective or objective method, lacking research with the methods combined, and under the impact of experimental apparatus, evaluation indices and evaluation standards, comparability among result of researches is not high [107]; while foreign research usually combines the two [108], being more comparable and scientifical in conclusions.…”
Section: Discussionmentioning
confidence: 99%